A Efek Kultivasi Konten Dakwah Felix Siauw Di Youtube Terhadap Generasi Muda Muslim - Abdul Azis; Reza Pahlevi Ginting (FKIP Universitas Palangka Raya, 2026)
The proliferation of social media, particularly YouTube, has reshaped the landscape of Islamic dakwah (preaching), notably among the young Muslim generation immersed in the digital ecosystem. Felix Siauw has emerged as a prominent preacher with considerable influence in this online sphere, distinguished by his argumentative, logical, and contextually relevant communication style. This study aims to examine the cultivation effects of Felix Siauw’s dakwah content on YouTube on the formation of religious perceptions and identity among young Muslims. Employing a descriptive qualitative approach anchored in George Gerbner’s cultivation theory, data were collected through in-depth interviews with five informants aged 18-30 years, observation of Felix Siauw’s YouTube content, and the gathering of digital documentation. Data analysis followed the Miles and Huberman model, reinforced by source and method triangulation to ensure the accuracy and reliability of the findings. The results reveal that repeated exposure to Felix Siauw’s dakwah materials cultivates ideological awareness and critical perspectives on social issues, while simultaneously strengthening the Islamic identity of young Muslims. This cultivation process facilitates a transformation in the understanding of religion, shifting it from mere ritual observance toward the conceptualization of Islam as a comprehensive value system and way of life. These findings affirm the applicability of cultivation theory within the realm of digital dakwah and underscore the imperative of media literacy for the younger generation.